Analysis of digital banking service perceptions and its impact on customer satisfaction among generation Z - Hartanti, Maysya; Kurniawan, Yohannes (Edelweiss Applied Science and Technology, 2025)
Digital banking has significantly altered financial services by facilitating transactions and financial management via online platforms. The swift growth of Indonesia’s digital banking sector underscores the necessity of comprehending the factors influencing Generation Z’s satisfaction to enhance service quality. As digital natives, Generation Z is crucial in driving growth within the sector. This research examines the primary elements affecting their satisfaction with digital banking services in Greater Jakarta, utilizing data collected from 400 participants. A structured questionnaire was employed, and the data were analyzed using the Structural Equation Model - Partial Least Square (SEM-PLS) method through SmartPLS 4.1.0.8, adopting an extended E-S-QUAL framework. The analysis evaluates efficiency, fulfillment, system availability, security, trust, convenience, and promotional policies. The findings indicate that efficiency, trust, convenience, and promotional policies significantly impact customer satisfaction. In contrast, fulfillment, system availability, and security exhibited no significant effect on customer satisfaction. Service providers must enhance these factors while re-evaluating less influential aspects. This study contributes to the existing literature on digital banking and offers practical recommendations for optimizing service quality. Future research should explore the moderating effects of gender and economic status, expanding the sample to include Millennials (Generation Y) for comparative insights.